Settlement in compensation cases against the background of sexual crimes committed by clergy of the Catholic Church - Sieczych-Drzewiecka, Alicja (Prawo Kanoniczne, 2023)
The purpose of this article is to discuss the practical aspects of a sexual offense settlement agreement. The work discusses key court decisions, both historical and contemporary, which allow the judicature to perceive the approach to the issue of settlement stability as well as to the legal problems related to this agreement. The article also discusses the procedural aspects of a settlement, in particular in the context of a court settlement. The basic scientific method is the dogmatic method, there are also a few comparative remarks in the work, especially in the field of US law. Conclusions from the work include a detailed discussion of the benefits and risks of a settlement concluded in a compensation for a tort – sexual abuse case. They also point to practical ways to make settlements more stable.